2018
DOI: 10.1002/job.2275
|View full text |Cite
|
Sign up to set email alerts
|

Changing the focus of locus (of control): A targeted review of the locus of control literature and agenda for future research

Abstract: Locus of control-a fundamental individual difference variable that reflects individuals' beliefsabout the degree of control they have over events in their lives-has been formally studied for more than 50 years. Early scholarship demonstrated that locus of control was a key predictor of various work-related outcomes, ranging from job attitudes and affect to motivation and behavior. Despite this evidence, the majority of contemporary organizational research has moved away from examining locus of control as an in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
126
1
5

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 152 publications
(155 citation statements)
references
References 125 publications
(242 reference statements)
3
126
1
5
Order By: Relevance
“…Our study suggests that MBA education can play an important role in helping students develop and enhance the specific psychological attributes of SE, EI, and LoC-I. People with these attributes appear to have a higher ability to identify important social cues in their environment and benefit from incidental learning situations (Lefcourt, 1976), which in turn helps them be more adaptive in the workplace (Dollinger & Taub, 1977) with higher EI being associated with higher leadership effectiveness (Rosete & Ciarrochi, 2005) and LoC-I being related to a wide range of positive work-related outcomes (Galvin et al, 2018). Importantly, the findings show that psychological competencies in EI, SE, and LoC-I can be developed, which may help refine MBA educational programs in their continuing effort to develop key knowledge, skills and ability outcomes.…”
Section: Discussionmentioning
confidence: 99%
“…Our study suggests that MBA education can play an important role in helping students develop and enhance the specific psychological attributes of SE, EI, and LoC-I. People with these attributes appear to have a higher ability to identify important social cues in their environment and benefit from incidental learning situations (Lefcourt, 1976), which in turn helps them be more adaptive in the workplace (Dollinger & Taub, 1977) with higher EI being associated with higher leadership effectiveness (Rosete & Ciarrochi, 2005) and LoC-I being related to a wide range of positive work-related outcomes (Galvin et al, 2018). Importantly, the findings show that psychological competencies in EI, SE, and LoC-I can be developed, which may help refine MBA educational programs in their continuing effort to develop key knowledge, skills and ability outcomes.…”
Section: Discussionmentioning
confidence: 99%
“…This is in line with Rotter's view that Locus of Control is a consequence of learning experiences. Consistently, the construct also exhibits a malleable, state-like property [49]. However, the gene-set GO_bp:go_cellular_response_to_ionizing_radiation was overrepresented amongst the LOCC results (see SI).…”
Section: Locus Of Control Over Diseasementioning
confidence: 69%
“…A great amount of research has reported the gaps between knowledge, values and action in environmental education (Heimlich & Ardoin, 2008). Internal LOC positively relates to variables such as empowerment, intrinsic task motivation (Galvin, Randel, Collins, & Johnson, 2018) and environmentally responsible behaviour (Kollmuss & Agyeman, 2002). Hence, LOC is a useful concept to practically work on the knowledge-value-action gap.…”
Section: Misol: Locus Of Control (Rotter)mentioning
confidence: 99%